Yaws in Africa: Past, Present and Future - Ezekiel K. Vicar; Shirley V. Simpson; Gloria I. Mensah; Kennedy K. Addo; Eric S. Donkor (Diseases)
Background: Yaws is an infectious, neglected tropical disease that affects the skin of many children and adolescents who live in poor, rural, low-income communities in humid, tropical areas of Africa, Southeast Asia, and the Pacific Islands. Yaws is currently endemic in at least 15 countries, but adequate surveillance data are lacking. In line with the WHO’s effort to improve early detection, diagnosis, and proper management leading to the eventual eradication of yaws, this article reviews the existing literature on yaws in Africa to highlight the epidemiological pattern, genetic variability, diagnosis modalities, treatment, and control strategies, the challenges and prospects for yaws eradication. Methods: We searched PubMed and Scopus databases to identify published data in line with the review objectives. Results: One hundred and eighty-eight peer-reviewed articles were identified by PubMed and Scopus, out of which thirty were eligible. The studies covered 11 African countries, with the reported prevalence ranging from 0.50% to 43.0%. Conclusions: There is a great prospect for eradication if countries capitalize on the availability of simple, inexpensive, and well-tolerated oral treatment that has proven effective, validated point-of-care diagnostic tests and new molecular tests. Countries should embark on integrated disease control efforts to increase sustainability and improve the quality of life for people living with this NTD in poor communities.